Characteristics the vicuña fleece (Vicugna vicugna mensalis) of Cala Cala and Picotani (Puno-Peru) reared in semicaptivity - Quispe Coaquira, Jesús E. (2019)
This paper shows the results of several research works on the characteristics of the fleece of vicuñas reared under semi-captivity conditions in the multicommunals of Cala Cala and Picotani, located in the province of San Antonio de Putina, Puno, Peru. The results indicate the presence of three color tones: light, dark and yellowish, whose extension in the body varies according to sex and age. In the praxis only the useful (commercial) part of the coat is sheared. The total weight of fleece shows variations between females (354.71 g) and males (364.65 g) (p<0.05). The fleece yields in vicuñas were similar by sex and body region, while the yield in juveniles was 84.43% and in adults 81.87% (p<0.05). The proportion of clean fleece reaches 80%. The proportion of hair in the fleece shows variations according to sex, age, body region and rearing locality.